Propagador electromagnético 3D para antenas ópticas integradas. - Vega-García, José Luis; Moreno-Pozas, Laureano; Barona-Ruiz, Miguel; Sánchez-Sánchez, Alejandro; Ortega-Moñux, Alejandro; Halir, Robert; Molina-Fernández, Íñigo; Wanguemert-Pérez, Juan Gonzalo (My University, 2025)
Accurate modeling of electromagnetic propagation is crucial for the design and optimization of integrated optical antennas, with applications in chip-to-fiber coupling, beam shaping, and free-space optical (FSO) communications. This work presents a 3D electromagnetic propagator based on the angular spectrum method, capable of computing the field evolution over both near-field and far-field regimes without paraxial approximations. The proposed approach enables precise long-distance propagation, maintaining a integral overlap with the analytical solution for Gaussian beams over distances up to tens of kilometers. Additionally, we provide simple analytical expressions to configure simulation parameters, ensuring numerical accuracy and computational efficiency. The tool is validated through two case studies: (i) long-distance Gaussian beam propagation in free space and (ii) near-field characterization of an integrated optical antenna for fiber coupling. The results confirm the versatility and accuracy of the proposed propagator for photonic applications.
Keywords: Fotónica; Silicio; Gauss, Aplicaciones de; Ondas electromagnéticas; Difracción; Antenas; Silicon photonics; Gaussian beam; Integrated optical antennas; Angular spectrum; Near field; Far field; Diffraction